2015
DOI: 10.2903/j.efsa.2015.4321
|View full text |Cite
|
Sign up to set email alerts
|

Risks for human and animal health related to the presence of phorbol esters in Jatropha kernel meal

Abstract: Following a request from the European Commission, the risks for human and animal health related to the presence of phorbol esters (PEs) in Jatropha kernel meal were assessed by the EFSA Panel of Contaminants in the Food Chain (CONTAM). Jatropha curcas (Jatropha) seeds contain substantial amounts of extractable oil utilised for biodiesel production. The remaining protein‐rich products (seed meal or kernel meal) may be used as a protein source in animal feed after removal of anti‐nutritive factors and toxic PEs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 112 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…The Panel made a theoretical exposure calculation to PEs possibly present in the NF (Section 3.8.4) and took into account uncertainties in the analytical method, by considering an LOD corrected with a factor of two (1.5 instead of the 0.75 lg PEs/g de-shelled kernel (as TPA equivalent) as reported in the specifications). Margins of exposure to the NOAEL (no observed adverse effect level) of 0.4 mg PEs/kg bw per day as identified by EFSA CONTAM Panel (2015) are reported in Table 13.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Panel made a theoretical exposure calculation to PEs possibly present in the NF (Section 3.8.4) and took into account uncertainties in the analytical method, by considering an LOD corrected with a factor of two (1.5 instead of the 0.75 lg PEs/g de-shelled kernel (as TPA equivalent) as reported in the specifications). Margins of exposure to the NOAEL (no observed adverse effect level) of 0.4 mg PEs/kg bw per day as identified by EFSA CONTAM Panel (2015) are reported in Table 13.…”
Section: Discussionmentioning
confidence: 99%
“…If a non-edible kernel is ingested, clinical symptoms include burning and pain in the mouth or throat and vomiting and this intoxication is generally self-limiting. However, it is reported that sometimes dizziness, nausea, abdominal pain and severe diarrhoea may occur and a few cases of more severe symptoms are also reported, mainly in children due to ingestion of a number of kernels (Devappa et al, 2010a;Shah and Sanmukhani, 2010;Chomchai at al., 2011;EFSA CONTAM Panel, 2015;Langrand et al, 2015;Gupta et al, 2016).…”
Section: Human Datamentioning
confidence: 99%
See 2 more Smart Citations